A real-world data analysis of montelukast in FDA Adverse Event Reporting System (FAERS) database - Hesen Huang; Kaiqin Chen; Yu Du; Jing Gao; Yixian Ye; Wei Lin (BMC Pharmacology and Toxicology)
Abstract Background Montelukast(MTK) is a leukotriene receptor antagonist widely used clinically for treating asthma and rhinitis. However, many adverse events (AEs) have been reported. In this study, we aimed to investigate MTK’s adverse drug reactions (ADRs) using real data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods We assessed the disproportionality of MTK-associated AEs by calculating metrics such as the ratio of reported ratios (ROR), proportional reporting ratios (PRR), Bayesian Belief Propagation Neural Networks (BCPNN), and Gamma-Poisson Shrinkers (GPS). Results From 2004 to the third quarter of 2023, of the 20,340,254 case reports in the FAERS database, 86,732 MTK reports were recorded as “principal suspect (PS)” AEs.Disproportionate analyses identified 431 preferred terms (PTs) associated with MTK in 27 organ systems. Unexpected major AEs were noted, such as Suffocation feeling, Adrenal suppression, Sudden visual loss and Endocardial fibrosis, none of which were mentioned in the drug insert. Conclusion Our findings are consistent with clinical observations highlighting potential new and unexpected ADR signals associated with MTK. Further prospective clinical studies are needed to confirm and elucidate the relationship between MTK and these ADRs. This study provides a fresh and unique perspective on the study of adverse drug events.